The Necessity of Individualized Education for Sharing Satisfaction - Yoon, Hee Sang (International Journal of Psychosocial Rehabilitation, 2020)
Sharing, expressed as a life-to-life exchange, is a unique characteristic that only humans can have in the Fourth Industrial Age. Sharing is a concept that can achieve a co-existence society and presents a direction for the future by forming a dynamic social network with tools. The trait of sharing is satisfaction based on sharing. By measuring the satisfaction of sharing, a system of feedback can be organized to effectively provide sharing education. For effective sharing education, it is a meaningful way to apply appropriate teaching methods according to temperament.This study shows that the education of sharing that affects the satisfaction of sharing can change according to the characteristics of the learner. It also shows that the satisfaction level of sharing can be increased according to the learner's past experience or differentiated education according to current.In this studywe use the factor analysis to analyze the survey of students at K University in Seoul on the knowledge, attitude, practice and practice of sharing. We also show that the satisfaction of sharing is independently influenced by the characteristic classified according to Pythagoras' defensive studies using the regression and path analysis.